Petrografia e geoquímica orgânica das escombreiras de carvão da Bacia Carbonífera do Douro - implicações ambientais - J. Ribeiro (2010)
The coal waste piles that result from Douro Coalfield exploitation represent one of the most significant environmental impacts caused by mining activities. The aim of this work is the petrographic and geochemical characterization of the organic fraction of fifteen coal waste piles, to identify and understand potential impacts on the environment. The data point to the existence of oxidation, acid drainage and consequently, the leaching of elements to the environment. The self-combustion processes in three coal waste piles enhance the acid drainage and leaching